KETERAMPILAN MEMBUAT KRIPIK UBI MELALUI METODE TUTOR SEBAYA PADA ANAK TUNAGRAHITA RINGAN KELAS VII DISLB YAPEM TARUSAN - Resfayeni - - (Universitas Negeri Padang, 2014)
This research was conducted based on the problem found in the field showed that there were four student with light mental retardation learning how to make purple sweet potato crisp but they got difficulties in acquiring the skill. This was a classroom action research which was conducted collaboratively with peers in two cycles. The first cycle consited of five meeting and second cycle consited of four meeting which were started from pre-activities, wilst activities and post-activities. The data was collected through observation and test. It then was analyzed qualitatively andquantitavely. The result of the pre-tes showed that the ability of AN was 85%, DW was 80%, AM was 0% and FD was 5%. In the first cycle the score gottem by AN was 100%, DW was 100%, AM was 50% and FD was 60%. In the second cycle AN got 100%, DW got 100%, AM got 100% and FD got 100%. These result indicated that there was an improvement on the student’s skill after peer-tutoring help was applied. Therefore, it was suggested to the teacher to involve the more skillful student in helping their peers to acquire certain skill so that those with light mental retardation were able to live independetly both in family and in society, and were able to live prosperously as they had life-skills for their future